Transformasi Karakter Anak Usia Dini lewat Pendidikan Nonformal di RTQ Al-Muwaffaq Kabupaten Bulukumba - Ilmar Andi Achmad; Emirati Emirati; Muhammad Athar Asmas (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Character formation and moral development for children are notonly obtained from formal institutions, but also non-formalinstitutions such as RTQ (Rumah Tahfidz Al-Qur'an) which havea role in forming good character. This study aims to determinethe Role of RTQ (Rumah Tahfidz Al-Qur'an) Al-Muwaffaq in theFormation of Early Childhood Character in Batukaropa Village,Bulukumba Regency. This study uses a qualitative method witha descriptive approach. Data collection techniques useobservation, interview and documentation techniques. Dataanalysis used is qualitative data analysis with data collectionsteps, data reduction, data presentation and drawingconclusions. Proof of data validity using triangulation techniques.The triangulation used is the combination of data sources withother data sources. The results of the study indicate that thereare several roles of the Al-Muwaffaq Al-Qur'an Tahfidz House inthe Formation of Early Childhood Character in BatukaropaVillage, Bulukumba Regency. First, the Al-Muwaffaq Al-Qur'anTahfidz House as a facilitator. Second, Al-Muwaffaq Al-QuranTahfidz House as a companion and supervisor. And third, AlMuwaffaq Al-Quran Tahfidz House as a motivator.